Contributions from the geomechanics laboratory (ECG-UCR) to the study of landslides in Costa Rica: The past 25 years - Mora, Rolando (2014)
It is a brief journey through the last 25 years of his research on landslides, together with Geomechanics Laboratory of the Central American School of Geology. How incomprehensible resulted the Geomorphology for decision makers is emphasized, which led to develop advanced research on the instability of natural and manmade slopes. This research process has experienced continuous growth, which began with studies on susceptibility to landslides, grew up with the probabilistic analysis of landslide hazard and detailed studies, and does not stop, it has now initiated the investigation related to landslide risk. Despite having this kind of progress, our decision-makers are still making bad decisions, but this has not discouraged us, on the contrary, it has been allowed us to grow and so is intended to continue.